'Exploring the emotional labour process experiences among black high school teachers in township schools - Machastella, Nkosinamandla (Rhodes University, 2026)
This study explores the emotional labour experiences of township black high school teachers, building upon Arlie Hochschild’s sociological concept of emotional labour. Through the emotional labour process lens, this study explores how teachers, like other service workers, perform, manage, and negotiate emotional labour within their interpersonal relationships and institutional school demands. This study focuses on the triadic relationships that shape and structure teachers’ daily interactions with learners, colleagues, and the school management team. To deepen the analysis, the study incorporates key concepts from the labour process theory - including managerial control and consent, autonomy, alienation, (de)skilling, and resistance (agency) to examine how power dynamics, collegial relations, and broader school working conditions shape these triadic interactions. While international research has increasingly examined emotional labour among teachers, few studies in South Africa have engaged critically with this phenomenon, particularly in relation to the intersections of school leadership, collegiality, and learner behaviour within township school settings. This study was conducted to contribute to this gap by exploring the emotional labour process experiences of high school teachers in township schools. A qualitative research design underpinned by critical realism guided the study, focusing on black township high school teachers in Sarah Baartman District Municipality, Eastern Cape. Data was collected through in-depth, semi-structured interviews with eight teachers of different genders, ages (experience), and professional positions. Interviews were audio-recorded, transcribed and thematically analysed using a qualitative critical framework aligned with the study’s four subsidiary goals. The findings reveal heightened emotional labour among teachers, shaped by three main factors: (1) teachers’ gender, age (experience), and professional positions; (2) the unique socio-economic challenges of the schools and surrounding communities, which affect learners and spill over into the school context; and (3) poor working conditions, including problematic learner behaviour, lack of active parenting, school services such as counselling provided to learners, weak collegial relationships, and insufficient institutional support, all of which intensify teachers’ emotional labour experiences. The study concludes with recommendations for mitigating these challenges and offers directions for future research on emotional labour within educational sociology.
a case of Sarah Baartman District Municipality, Eastern Cape, South Africa'
Keywords: Uncatalogued